Predictors of Results of Living Relative Donor Kidney Transplantation in Children - V. A. Goryaynov; M. M. Kaabak; N. N. Babenko; M. M. Morozova; L. I. Agureyeva; A. G. Aganesov; E. N. Platova; O. V. Dymova; V. V. Panin (Педиатрическая фармакология, 2015)
Relevance. Successful living relative donor (LRD) kidney transplantation is the most effective method of treating children with terminal chronic renal failure. Materials and methods. 148 living relative donor kidney transplantations to children were performed at the department of kidney transplantation of the Federal State Budgetary Research Institution “Academician Petrovskiy Russian Surgical Research Center” from December 2012 to March 2015. We used the following parameters to evaluate the factors affecting results of such an operation: recipient’s age and sex; living relative donor’s age and sex; antigen donor/recipient compatibility (system HLA-A, -B, -DR); type of induced immunosuppression; donor/recipient degree of kindred; presence or absence of rejection episodes throughout the whole observation period. Student’s test, Fisher’s test and Kaplan–Meier’s cumulative survival analysis of recipients and transplants were used for statistical processing. Results. 4 allokidneys out of 71 were rejected in group 1 (5.63%), in group 2 — 4 out of 77 (5.19%). The relative rates of transplant and patient survival were higher if LRD were 24–40 years of age than if LRD were 41–68 years of age. 12 patients out of 77 died in group 1 (15.58%), in group 2 — 3 out of 65 (4.62%). 7 allokidneys out of 67 were rejected in girls (7 fatal outcomes), in boys — 6 out of 81 (8 fatal outcomes). The highest rates of fatal outcomes and transplant rejection were observed in the group of patients prescribed daclizumab for induced immunosuppression, the lowest — in the group of patients prescribed methyl prednisolone. Conclusion. The conducted clinical material analysis led us to a conclusion that only two factors affect results of relative donor kidney transplantation in children — antigen donor/recipient compatibility (system HLA-A, -B, -DR) and presence of rejection episodes in the posttransplantation period.